Relationship of urinary endothelin-1 with estimated glomerular filtration rate in autosomal dominant polycystic kidney disease: a pilot cross-sectional analysis. Issue 1 (December 2016) - Raina, Rupesh; Lou, Linda; Berger, Bruce; Vogt, Beth; Do, Angelique; Cunningham, Robert; Vasavada, Pauravi; Herrmann, Karin; Dell, Katherine; Simonson, Michael
Abstract Background The pathogenesis of progressive renal insufficiency in autosomal dominant polycystic kidney disease (ADPKD) is unclear. Evidence from experimental models of ADPKD suggests that elevated endothelin-1 (ET-1) drives cyst growth, renal fibrosis and loss of renal function, but whether ET-1 is elevated in humans with ADPKD is uncertain. Methods In a cross-sectional study of ADPKD we measured urinary ET-1, a surrogate for ET-1 in kidney cortex, in spot collections corrected for creatinine. The volume of each kidney was measured using MRI-based stereology. The relationship of urine ET-1 with MDRD eGFR and kidney volume was modeled by multiple linear regression with adjustment for clinical covariates. Results Patients with ADPKD were ages 18 to 53 with eGFRs (median, interquartile range) of 63.2 (43.5–80.2) ml/min/1.73 m2 and albumin/creatinine ratios (ACR) of 115.0 (7.5–58.5) μg/mg. Urine ET-1 was inversely associated with eGFR (r = −0.480, P < 0.05) and positively (r = 0.407, P = 0.066) with ACR independent of age and female sex (P < 0.01). ET-1 appeared to be positively associated with total kidney volume (r = 0.426, P = 0.100), with a test for trend across urine ET-1 quartiles yieldingz = 1.83, P = 0.068. ET-1 strongly correlated with NAGase (r = 0. 687, P = 0.001), a marker of tubular damage and a surrogate marker of renal disease progression in ADPKD. Of note, ET-1 levels in urine were not correlated with hypertension. Conclusions In a translational study of patients with ADPKD, urinary ET-1 was inversely associated with eGFR and positively correlated with total kidney volume. Taken together with results from experimental models, these findings suggest that the role of ET-1 in ADPKD warrants further investigation.